Case Report: Deep and durable PSA response to same-agent enzalutamide rechallenge in metastatic castration-resistant prostate cancer without chemotherapy - Chen, Huan; Wang, Yan; Qu, Min; Gao, Xu (Frontiers in Oncology, 2026)
Contemporary guidelines recommend docetaxel as first-line chemotherapy for chemotherapy-naïve men with metastatic castration-resistant prostate cancer (mCRPC) who progress on an androgen receptor signaling inhibitor (ARSI). Cabazitaxel is preferred after prior docetaxel and one ARSI. However, real-world constraints—such as patient preference, access, or comorbidity—often preclude chemotherapy, and cross-resistance among ARSIs is common, making robust responses to same-agent rechallenge uncommon. We report a 74-year-old man diagnosed in 2015 with de novo metastatic hormone-sensitive prostate cancer (Gleason 4 + 4; cT4N1M1b). Under continuous medical castration, he received sequential first- and next-generation ARSIs but consistently declined chemotherapy and radiotherapy. Following biochemical progression on enzalutamide in early 2025, which was accompanied by imaging findings suggestive of a new T12 lesion, and after a brief bicalutamide interval, enzalutamide was rechallenged under a time-limited, PCWG3-aligned protocol with predefined stop rules. Over five months, prostate-specific antigen (PSA) levels declined from 17.73 ng/mL to 2.62 ng/mL (~85% reduction); this PSA response was maintained for ≥5 months through the last follow-up while the patient remained on enzalutamide, without new adverse events or increased analgesic use. This case suggests that in a preference-constrained, chemotherapy-naïve patient, same-agent enzalutamide rechallenge can yield a clinically meaningful PSA response. The observation raises the hypothesis that ARSI resistance may be reversible in a subset of patients, warranting prospective evaluation of biomarker-guided rechallenge strategies to optimize patient selection and minimize opportunity cost.